(untitled) (Signifiances (Signifying), 2022)
This paper aims to contribute to a linguistics of individuals through the reflexive overview of fieldwork with Nahua speakers in Mexico. First, sociolinguistic stigma as evidenced in language experiences will be examined to show that the local metalanguage is an important key to improving the “academic” metalanguage, as well as to build a sense of vindication of Nahuatl as spoken in Santa Catarina (Morelos). Second, we examine other Nahuan regions where a similar approach -alternating between theory and practice- has been applied to develop literacy workshops: Tepetitlán (Oaxaca) and Mecayapan (Veracruz). At both metadiscursive and linguistic levels, speakers show considerable sociolinguistic variation in promoting the construction of communicative strategies for a better understanding of dialectal diversity in the Nahua world.